Taxation of public budget revenues by the non-profit making organizations - Březovská, Žaneta; Slintáková, Barbora; Schvábová, Andrea; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2010)
The aim of this work is to find an incidence of taxation of public budget revenues on a tax base and a resulting tax by the non-profit making organizations. First is described possible resources financial from public budgets, which non-profit making organizations can receive. The rules of taxation of the public budget revenues and its comparison between corporate and non-profit sector is following. This revenue is not generally taxable by the non-profit making subjects, but there are some exeptions. Next it is analysis of some reasons for not taxation of this revenue. This work describes other revenue taxation because of a finding income tax by this tax payers. The calculation of income tax is analysed on a case study, where I set a values of revenues and expenses. In conclusion I anyses an incidence of taxation of public budget revenues on a tax base and a resulting tax by the non-profit making organizations.
Vedoucí práce: Barbora Slintáková
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2010
Rok obhajoby 2010
Keywords: zdanění a daňová politika [obor bakal. práce]; bakalářské práce; bachelor's theses